1996
DOI: 10.1073/pnas.93.21.12026
|View full text |Cite
|
Sign up to set email alerts
|

A plastid enzyme arrested in the step of precursor translocation in vivo.

Abstract: The key enzyme of chlorophyll biosynthesis in higher plants, NADPH:protochlorophyllide (Pchlide) oxidoreductase (POR, EC 1.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…1, lanes g and h versus e and f and SI Fig. 8A, lanes [11][12][13][14][15][16][17][18][19][20], we assumed that a factor may be present in wheat germ extract that triggered substrate-independent import of pPORA. Consistent with this view, import of reticulocytetranslated pPORA into Pchlide-free chloroplasts could be rescued by addition of wheat germ extract (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, lanes g and h versus e and f and SI Fig. 8A, lanes [11][12][13][14][15][16][17][18][19][20], we assumed that a factor may be present in wheat germ extract that triggered substrate-independent import of pPORA. Consistent with this view, import of reticulocytetranslated pPORA into Pchlide-free chloroplasts could be rescued by addition of wheat germ extract (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ivanova et al (12) and Kubis et al (13) discovered that the main presequence receptor atToc159 interacts with precursors to photosynthetic proteins, but it displayed little activity in binding assays with nonphotosynthetic precursors including that of NADPH:protochlorophyllide (Pchlide) oxidoreductase A (pPORA) (14). Import of this nucleus-encoded enzyme was shown to depend on the presence of Pchlide (15)(16)(17) and involve a translocon not identical with the Toc159-and Toc75-containing translocon used by photosynthetic precursors (18)(19)(20). Biochemical studies identified the pPORA translocon to consist of several unique components, called Pchlide-dependent translocon (Ptc) proteins, of which Ptc52 most likely operated as a Pchlide a oxygenase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous work, this 44-kDa protein most likely represented the cytosolic precursor of the pPORA (14). Import of this nucleusencoded plastid protein requires protochlorophyllide (Pchlide) (14)(15)(16)(17) and is due to the operation of an import pathway that has been proposed to be unique compared with the import pathways of other precursors (18).…”
mentioning
confidence: 99%
“…IB demonstrates that three POR-related proteins could be detected, displaying molecular masses of 44, 38 and 36kDa, respectively. According to our previous studies [24,46], these POR proteins were likely to represent the cytosolic precursor of the PORA, pPORA (44kDa), the mature PORB (38kDa) and the mature PORA (36kDa). Large-scale isolation from múltiple gels of the 44, 38 and 36kDa bands plus subsequent sequencing of proteolytic fragments generated with cyanogen bromide or different proteases confirmed that the 44kDa protein indeed represents the pPORA and its mature, 36kDa form, whereas the partial sequence information for the 38kDa band demonstrated that it is identical with PORB (Fig.…”
Section: Pora and Porb Are Developmentally Expressed Across The Barlementioning
confidence: 99%